Gel polymer electrolyte based on flame-retardant local high-concentration electrolyte as well as preparation method and application of gel polymer electrolyte

By using in-situ polymerization technology of local high-concentration electrolyte based on phosphate-based flame retardant local high-concentration electrolyte and polymer framework in lithium batteries, the problem of insufficient high voltage and thermal stability of traditional electrolytes is solved, and low impedance and high impedance are achieved Ion conductivity and excellent cycling performance significantly improve the safety and service life of the battery.

CN119297391APending Publication Date: 2025-01-10SHENZHEN JINTANG NEW ENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411447593.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The traditional carbonate electrolytes in existing lithium batteries have shortcomings in high voltage and thermal stability, and the challenges of phosphate-based electrolytes in negative electrode stability limit their commercial applications, and the high viscosity of local high concentration electrolytes and Cost issues need to be solved through diluents, which may bring about free solvent-related problems.

Method used

采用基于磷酯基的阻燃局部高浓度电解液,通过原位聚合技术将磷酸酯基电解液与聚合物骨架结合,优化锂盐及溶剂组成,形成特定的溶剂化结构,引入稀释剂以降低粘度并提高润湿性,显著降低可燃性,制备出低阻抗、良好浸润性、高离子电导率的凝胶聚合物电解质。

Benefits of technology

Achieve uniform deposition of lithium ions on the negative electrode surface, improve the stability and performance of the electrolyte, significantly improve the overall safety of the battery system, reduce cost problems, and in high-voltage NCM811||Li||MCMB full battery Excellent cycle performance is shown.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297391A_ABST
    Figure CN119297391A_ABST
Patent Text Reader

Abstract

The invention discloses a gel polymer electrolyte based on a flame-retardant local high-concentration electrolyte, a preparation method of the gel polymer electrolyte and application of the gel polymer electrolyte in a battery. The preparation method comprises the following steps: S1, mixing a lithium salt with a non-combustible phosphate solvent, and then adding a diluent to obtain a basic electrolyte; s2, dissolving a monomer and a free radical initiator in the basic electrolyte to form a precursor solution; and S3, carrying out reaction on the precursor solution at 60-80 DEG C for 4-24 hours to obtain the gel polymer electrolyte. The prepared gel polymer electrolyte has a unique ion solvation structure in a local high-concentration electrolyte, a good solid electrolyte interface film (SEI) can be formed, the in-situ preparation method of the polymer electrolyte can reduce the interface impedance, and the gel polymer electrolyte shows excellent performance in the aspects of stabilizing a nickel-rich positive electrode interface and adjusting the lithium deposition form. While good electrochemical stability of a phosphatide-based electrolyte with good flame retardance and a high-nickel lithium metal battery system is considered, the construction mode of an anion-rich solvation structure is expanded.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a gel polymer electrolyte based on a flame-retardant local high-concentration electrolyte, and a preparation method and application thereof. Background Art

[0002] As the global demand for energy continues to rise, electric vehicles and renewable energy storage technologies are becoming increasingly important. Although lithium metal anodes were once ignored due to safety concerns caused by dendrite problems, researchers have regained interest in them given their low potential (-3.04V relative to standard hydrogen electrode) and high specific capacity (3860mAh / g). The formulation of the electrolyte is crucial to the performance, cycle life and safety of the battery, and has therefore become a focus of research. Traditional carbonate-based electrolytes have shortcomings in high voltage and thermal stability, which requires the development of new, non-flammable electrolytes that are compatible with lithium metal anodes and high-voltage cathodes. In recent years, researchers have explored a variety of non-flammable electrolytes including phosphate-based, solid-state, ionic liquid and fluorinated electrolytes. In particular, the free radicals generated by phosphate groups when decomposed help reduce flammability, making them a potential safe electrolyte option. However, the challenges of phosphate-based electrolytes in anode stability limit their commercial application.

[0003] Locally highly concentrated electrolytes (LHCEs) have attracted attention due to their great potential for the commercialization of lithium metal batteries (LMBs). In these electrolytes, the anions of lithium salts dominate the formation of contact ion pairs (CIPs) and ion aggregates (AGGs), which facilitate the uniform deposition of lithium ions on the anode surface. However, the high viscosity and cost issues of the electrolyte need to be addressed by introducing diluents to reduce the viscosity and improve the wettability. Nevertheless, the increase in the diluent ratio may bring about free solvent-related issues.

[0004] Meanwhile, gel polymer electrolytes (GPEs) have attracted attention due to their stability during the liquid-to-gel transition. These electrolytes can be formed by in situ polymerization and can serve as functional additives to help form a stable electrode interface. To overcome existing challenges, researchers are seeking to develop a new type of gel polymer electrolyte that should be easy to prepare, have low resistance, good wettability, high ionic conductivity, high oxidation potential (to accommodate high voltage cathodes), and be compatible with LHCEs systems. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a gel polymer electrolyte based on a phosphite-based flame-retardant local high-concentration electrolyte, a preparation method thereof, and an application in a battery.

[0006] The present invention adopts the following technical solution:

[0007] A method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte, characterized in that it comprises the following steps:

[0008] S1, mixing a lithium salt with a non-flammable phosphate solvent, and then adding a diluent to the mixture of the lithium salt and the non-flammable phosphate to obtain a basic electrolyte, that is, a phosphate-based flame-retardant local high-concentration electrolyte;

[0009] S2, dissolving the monomer and the free radical initiator in the basic electrolyte obtained in step S1 according to a preset ratio to form a precursor solution;

[0010] S3. React the precursor solution at 60-80° C. for 4-24 hours to obtain a gel polymer electrolyte.

[0011] The lithium salt in the basic electrolyte in step S1 is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide salt (LiFSI), lithium hexafluorophosphate, lithium difluorophosphate, lithium nitrate (LiNO3), lithium tetrafluoroborate, lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate, and lithium trifluoromethanesulfonate.

[0012] The non-flammable phosphate solvent in the base electrolyte in step S1 is one or more of trimethyl phosphate (TMP), triethyl phosphate (TEP), tributyl phosphate, triphenyl phosphate, 4-isopropylphenyl diphenyl phosphate, diphenyl octyl phosphate, and trioctyl phosphate.

[0013] The diluent in the basic electrolyte in step S1 is one or more of 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether (HFE), bis(2,2,2-trifluoroethyl) ether (BTFE), methyl nonafluorobutyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE).

[0014] The volume ratio of the non-flammable phosphate solvent to the diluent added in step S1 is 2:1-1:4; the concentration of the lithium salt in the basic electrolyte is 1-3 mol / L.

[0015] The monomer added in step S2 is one or more of N,N'-methylenebisacrylamide (MBA), N,N-dimethylacrylamide (DMAA), ethoxylated trimethylolpropane triacrylate (ETPTA), pentaerythritol tetraacrylate (PETEA), polyethylene glycol dimethacrylate (PEGDMA), isopropenyl diethyl phosphate, and vinyl diethyl phosphate.

[0016] The free radical initiator added in step S2 is one of azobisisobutyronitrile (AIBN), cyclohexanone peroxide, azobisisoheptanenitrile, tert-butyl hydroperoxide, and dimethyl azobisisobutyrate.

[0017] The mass ratio of the monomer, the free radical initiator and the basic electrolyte added in step S2 is (2-10): (0.1-0.5): (98-90).

[0018] A gel polymer electrolyte obtained according to the above preparation method.

[0019] An application of the gel polymer electrolyte obtained according to the above preparation method in a battery, the battery comprising a high-voltage positive electrode, a negative electrode, a separator and the above gel polymer electrolyte; the high-voltage positive electrode is NCM811, and the negative electrode is one or more of lithium metal, graphite, and mesophase carbon microspheres.

[0020] The technical solution of the present invention has the following advantages:

[0021] A. The present invention utilizes in-situ polymerization technology to combine a phosphate-based electrolyte with a polymer skeleton to prepare a gel polymer electrolyte with low impedance, good wettability, high ionic conductivity and excellent safety performance. Combining the concept of local high concentration electrolytes (LHCEs), by optimizing the lithium salt and solvent composition, a specific solvation structure is formed, which promotes the uniform deposition of lithium ions on the negative electrode surface and improves the stability and performance of the electrolyte. By adopting non-flammable phosphate-based solvents, the flammability of the electrolyte is significantly reduced, and the overall safety of the battery system is improved. By introducing a diluent, the viscosity of the electrolyte is effectively reduced, the wettability is improved, and the cost problem caused by the high salt ratio is reduced, making the electrolyte more practical.

[0022] B. The electrolyte system designed in the present invention achieves high performance in high-voltage NCM811||Li batteries, and exhibits excellent cycling performance in assembled NCM811||MCMB full batteries, highlighting its great potential in practical applications.

[0023] C. The present invention constructs a unique anion-rich solvation structure, which performs well in stabilizing the nickel-rich positive electrode interface and regulating the lithium deposition morphology, further improving the cycle stability and service life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 The combustion test experimental diagram of the electrolyte prepared in Example 1 and Comparative Example 7;

[0026] Figure 2 This is a test diagram of the electrochemical stability window of the phosphate flame-retardant local high-concentration electrolyte and the gel polymer electrolyte of the present invention;

[0027] Figure 3 The SEM image of the lithium deposition morphology of the Li-NCM811 half-cell of the electrolyte described in Example 1 and the TEM image of the NCM811 positive electrode;

[0028] Figure 4 This is a cycle performance diagram of a Li-NCM811 half-cell assembled using the phosphate flame-retardant local high-concentration electrolyte prepared in Example 1.

[0029] Figure 5 This is the cycling performance diagram of the Li-NCM811 half-cell assembled with the gel polymer electrolyte prepared in Example 7.

[0030] Figure 6 The figure is a temperature dependence diagram of the ionic conductivity of the phosphate flame retardant local high concentration electrolyte and the gel polymer electrolyte of the present invention in the range of 30-80°C.

[0031] Figure 7 This is a cycle performance diagram of the MCMB-NCM811 full battery assembled using the phosphate flame-retardant local high-concentration electrolyte prepared in Example 1. DETAILED DESCRIPTION

[0032] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] This embodiment provides a method for preparing a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0035] First, trimethyl phosphate and TTE are mixed in a volume ratio of 1:1 to obtain a mixed solvent, and then 0.85M LiTFSI and 0.15M LiNO3 are dissolved in the mixed solvent, and stirred to form a homogeneous basic electrolyte, which is the phosphoester-based flame-retardant local high-concentration electrolyte.

[0036] Example 2

[0037] The difference from Example 1 is that trimethyl phosphate and TTE are mixed in a volume ratio of 1:4. Other substances, amounts and preparation methods are the same as those in Example 1.

[0038] Example 3

[0039] The difference from Example 1 is that trimethyl phosphate and TTE are mixed in a volume ratio of 2:1. Other substances, amounts and preparation methods are the same as those in Example 1.

[0040] Example 4

[0041] This embodiment provides a method for preparing a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0042] Trimethyl phosphate and TTE are mixed in a volume ratio of 1:1, and then 2.5M LiTFSI, 0.1M LiFSI, and 0.4M LiNO3 are dissolved in the mixed solvent and stirred to form a homogeneous basic electrolyte, which is the phosphoester-based flame-retardant local high-concentration electrolyte.

[0043] Example 5

[0044] This embodiment provides a method for preparing a gel polymer electrolyte based on a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0045] 2 wt % N,N'-methylenebisacrylamide and 0.2 wt % AIBN were added to the basic electrolyte of Example 1 to obtain a precursor solution, and the precursor solution was added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 4 hours to obtain a gel polymer electrolyte.

[0046] Example 6

[0047] This embodiment provides a method for preparing a gel polymer electrolyte based on a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0048] 3 wt % N,N'-methylenebisacrylamide and 0.3 wt % AIBN were added to the basic electrolyte of Example 1 to obtain a precursor solution, and the precursor solution was added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 6 hours to obtain a gel polymer electrolyte.

[0049] Example 7

[0050] This embodiment provides a method for preparing a gel polymer electrolyte based on a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0051] 5 wt % N,N'-dimethylacrylamide (DMAA) and 0.5 wt % AIBN were added to the basic electrolyte of Example 1 to obtain a precursor solution, which was then added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 80°C for 10 hours to obtain a gel polymer electrolyte.

[0052] Example 8

[0053] This embodiment provides a method for preparing a gel polymer electrolyte based on a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0054] 2 wt % of N,N'-methylenebisacrylamide (MBA), 2 wt % of ethoxylated trimethylolpropane triacrylate and 0.4 wt % of AIBN were added to the base electrolyte of Example 1 to obtain a precursor solution, which was added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 24 hours to obtain a gel polymer electrolyte.

[0055] Example 9

[0056] This embodiment provides a method for preparing a gel polymer electrolyte based on a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0057] 5 wt % of N,N'-dimethylacrylamide (DMAA), 2 wt % of ethoxylated trimethylolpropane triacrylate and 0.4 wt % of AIBN were added to the base electrolyte of Example 1 to obtain a precursor solution, which was then added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 16 hours to obtain a gel polymer electrolyte.

[0058] Example 10

[0059] This embodiment provides a method for preparing a gel polymer electrolyte based on a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0060] 2 wt % N,N'-methylenebisacrylamide (MBA) and 0.2 wt % AIBN were added to the electrolyte of Example 4 to obtain a precursor solution, which was then added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 70°C for 4 hours to obtain a gel polymer electrolyte.

[0061] Embodiment 11

[0062] This embodiment provides a method for preparing a gel polymer electrolyte based on a phosphoester-based flame-retardant local high-concentration electrolyte, comprising the following steps:

[0063] S1. First, trimethyl phosphate and TTE are mixed in a volume ratio of 1:1, and then 1M LiTFSI, 0.15M LiNO3, 0.03M LiFSI, and 0.01M LiDFOB are dissolved in a mixed solvent, and the mixture is stirred to form a homogeneous electrolyte. The mixture is stirred to form a homogeneous electrolyte.

[0064] S2, then adding 2wt% of N,N'-methylenebisacrylamide (MBA) and 0.2wt% of AIBN to obtain a precursor solution;

[0065] S3, add the precursor solution to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 6 hours to obtain a gel polymer electrolyte.

[0066] Example 12

[0067] The difference from Example 11 is that 0.03M LiFSI and 0.01M LiDFOB are replaced by 0.2M LiFSI and 0.02M LiDFOB. Other substances, amounts and preparation methods are the same as those in Example 11.

[0068] Comparative Example 1

[0069] First, trimethyl phosphate and TTE are mixed in a volume ratio of 1:1, and then 1M LiTFSI is dissolved in the mixed solvent, and stirred to form a homogeneous electrolyte, which is a phosphoester-based flame-retardant electrolyte that does not contain LiNO3.

[0070] Comparative Example 2

[0071] 2M LiTFSI was dissolved in pure trimethyl phosphate solvent.

[0072] Comparative Example 3

[0073] 2 wt% N,N'-methylenebisacrylamide (MBA) and 0.2 wt% AIBN were added to a commercial electrolyte (1 M LiPF6 dissolved in EC and DEC with a volume ratio of 1:1, 5% FEC) to obtain a precursor solution, which was then added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 4 hours to obtain a comparative gel polymer electrolyte.

[0074] Comparative Example 4

[0075] 2 wt % of N,N'-methylenebisacrylamide (MBA) and 0.2 wt % of AIBN were added to a commercial electrolyte (1 M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) to obtain a precursor solution without heating.

[0076] Comparative Example 5

[0077] 2 wt% N,N'-methylenebisacrylamide (MBA), 2 wt% ethoxylated trimethylolpropane triacrylate, and 0.2 wt% AIBN were added to a commercial electrolyte (1 M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) to obtain a precursor solution, which was added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 4 hours to obtain a comparative gel polymer electrolyte.

[0078] Comparative Example 6

[0079] 5 wt% N,N'-dimethylbisacrylamide (DMAA), 2 wt% ethoxylated trimethylolpropane triacrylate, and 0.5 wt% AIBN were added to a commercial electrolyte (1 M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) to obtain a precursor solution, which was added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1O2) as the positive electrode, lithium metal as the negative electrode, and a polypropylene film as the separator, and then heated in an oven at 60°C for 4 hours to obtain a comparative gel polymer electrolyte.

[0080] Comparative Example 7

[0081] A commercial electrolyte (1M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) was added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and polypropylene film as the separator.

[0082] Battery construction:

[0083] Positive electrode preparation: The positive electrode material LiNi 0.8 Co 0.1 Co 0.1 O2 (NCM811), binder polyvinylidene fluoride (PVDF), conductive agent acetylene black and N-methylpyrrolidone (NMP) were mixed evenly and stirred for 12 hours. The mass ratio of positive electrode material, PVDF and acetylene black was 9:0.5:0.5 to obtain positive electrode slurry. The obtained slurry was coated on the surface of aluminum foil, and then the electrode was dried in a vacuum oven (80°C, 12h). After drying, the positive electrode was cut into discs with a punching machine and placed in an argon atmosphere glove box for standby use.

[0084] Negative electrode preparation: Mix the negative electrode material mesophase carbon microspheres (MCMB), binder polyvinylidene fluoride (PVDF), conductive agent acetylene black, carbon nanotubes and N-methylpyrrolidone (NMP) evenly and stir for 12 hours. The mass ratio of negative electrode material, PVDF, acetylene black and carbon nanotubes is 91:6:2.5:0.5 to obtain negative electrode slurry. The obtained slurry is coated on the surface of copper foil, and then the electrode is dried in a vacuum oven (80℃, 12h). After drying, the negative electrode electrode is cut into discs with a punching machine and placed in an argon atmosphere glove box for standby use.

[0085] Button cell construction: stack the negative electrode shell, negative electrode, and separator in the center in sequence, then add 70ul of the corresponding electrolyte, and after it moistens the separator, stack the NCM811 positive electrode, gasket, spring, and positive electrode shell in the center in sequence, and finally place the whole into the battery sealing machine for compaction, and let it stand for 24 hours before use.

[0086] Figure 1 The combustion test experiment of the electrolytes prepared in Example 1 and Comparative Example 7 shows that the phosphate flame-retardant local high-concentration electrolyte prepared in Example 1 exhibits a high degree of non-flammability.

[0087] Figure 2The electrochemical stability window test of phosphate flame retardant local high concentration electrolyte and gel polymer electrolyte. It can be seen from the figure that the electrolyte described in this embodiment has a wide electrochemical stability window, the highest oxidation potential is 5.1V, strong oxidation resistance, and can be applied to high voltage battery systems.

[0088] Figure 3 These are the SEM and TEM images of the electrolyte described in Example 1. It can be seen that in the electrolyte described in this example, the Li deposition morphology is flat and dense, and the NCM811 positive electrode particles maintain a complete structure, which shows that the side reaction between Li and TMP is fully suppressed to form a stable SEI and uniform CEI.

[0089] Figure 4 The cycle performance diagram of the Li-NCM811 half-cell assembled with the phosphate flame-retardant local high-concentration electrolyte prepared in Example 1 has a voltage range of 2.8-4.5V. The diagram shows that under 1C rate conditions, after 200 cycles, the measured battery specific capacity remains stable, the cycle coulomb efficiency reaches 99.2%, and the capacity retention rate is 93.3%.

[0090] Figure 5 The cycle performance diagram of the Li-NCM811 half-cell assembled with the gel polymer electrolyte prepared in Example 7 has a voltage range of 2.8-4.3V. The diagram shows that under the condition of 0.5C rate, after 100 cycles, the measured battery specific capacity remains stable, and the capacity retention rate is 91.1%.

[0091] Figure 6 It is the temperature dependence of the ionic conductivity of the phosphate flame retardant local high concentration electrolyte and the gel polymer electrolyte in the range of 30-80° C. It can be seen that the activation energy of the gel polymer electrolyte in this embodiment is lower than that of the liquid local high concentration electrolyte (0.143 eV), indicating that after gelation, ions are quickly transported through the polymer chain, proving the low ion transport energy barrier.

[0092] Figure 7 The cycle performance diagram of the MCMB-NCM811 full battery assembled with the phosphate flame-retardant local high-concentration electrolyte prepared in Example 1 is shown in the voltage range of 2.3-4.3V and the N / P ratio of 1. The figure shows that under the condition of 0.5C rate, after 300 cycles, the measured battery specific capacity remains stable, and the capacity retention rate is 83%, indicating that the prepared electrolyte is very practical.

[0093] The present invention deeply explores various key practical properties of phosphate-based electrolytes, and some recent insights into the solvation structure of local high-concentration electrolytes are consolidated and extended. In addition, it is found that the LiNO3-induced interfacial decomposition mechanism acts on the two electrode interfaces, which helps the designed electrolyte system to achieve high performance in high-voltage NCM811||Li batteries. In addition, excellent cycling performance is achieved in the assembled NCM811||MCMB full battery, highlighting its practical value. A phosphate-based electrolyte with good flame retardancy is mixed with a polymer skeleton and a gel polymer electrolyte is prepared by in situ polymerization. A unique anion-rich solvation structure is constructed, which exhibits excellent performance in stabilizing the nickel-rich cathode interface and regulating the lithium deposition morphology.

[0094] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.

Claims

1. A method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte, characterized in that: The steps include: S1, mixing a lithium salt with a non-flammable phosphate solvent, and then adding a diluent to the mixture of the lithium salt and the non-flammable phosphate to obtain a basic electrolyte, that is, a phosphate-based flame-retardant local high-concentration electrolyte; S2, dissolving the monomer and the free radical initiator in the basic electrolyte obtained in step S1 according to a preset ratio to form a precursor solution; S3. React the precursor solution at 60-80° C. for 4-24 hours to obtain a gel polymer electrolyte.

2. The method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte according to claim 1, characterized in that: The lithium salt in the basic electrolyte in step S1 is one or more of lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide salt (LiFSI), lithium hexafluorophosphate, lithium difluorophosphate, lithium nitrate (LiNO3), lithium tetrafluoroborate, lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate, and lithium trifluoromethanesulfonate.

3. The method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte according to claim 1, characterized in that: The non-flammable phosphate solvent in the base electrolyte in step S1 is one or more of trimethyl phosphate (TMP), triethyl phosphate (TEP), tributyl phosphate, triphenyl phosphate, 4-isopropylphenyl diphenyl phosphate, diphenyl octyl phosphate, and trioctyl phosphate.

4. The method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte according to claim 1, characterized in that: The diluent in the basic electrolyte in step S1 is one or more of 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether (HFE), bis(2,2,2-trifluoroethyl) ether (BTFE), methyl nonafluorobutyl ether, and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE).

5. The method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte according to claim 1, characterized in that: The volume ratio of the non-flammable phosphate solvent to the diluent added in step S1 is 2:1-1:4; the concentration of the lithium salt in the basic electrolyte is 1-3 mol / L.

6. The method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte according to claim 1, characterized in that: The monomer added in step S2 is one or more of N,N'-methylenebisacrylamide (MBA), N,N-dimethylacrylamide (DMAA), ethoxylated trimethylolpropane triacrylate (ETPTA), pentaerythritol tetraacrylate (PETEA), polyethylene glycol dimethacrylate (PEGDMA), isopropenyl diethyl phosphate, and vinyl diethyl phosphate.

7. The method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte according to claim 1, characterized in that: The free radical initiator added in step S2 is one of azobisisobutyronitrile (AIBN), cyclohexanone peroxide, azobisisoheptanenitrile, tert-butyl hydroperoxide, and dimethyl azobisisobutyrate.

8. The method for preparing a gel polymer electrolyte based on a flame retardant local high concentration electrolyte according to claim 1, characterized in that: The mass ratio of the monomer, the free radical initiator and the basic electrolyte added in step S2 is (2-10): (0.1-0.5): (98-90).

9. A gel polymer electrolyte obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the gel polymer electrolyte obtained by the preparation method according to any one of claims 1 to 8 in a battery, characterized in that: The battery comprises a high-voltage positive electrode, a negative electrode, a separator and a gel polymer electrolyte; the high-voltage positive electrode is NCM811, and the negative electrode is one or more of lithium metal, graphite and mesophase carbon microspheres.

Citation Information

Cited By

  • Local high-concentration flame-retardant gel polymer electrolyte, battery and preparation method thereof

    CN121662964A

  • High-concentration localized flame-retardant gel polymer electrolyte, battery and its preparation method

    CN121662964B